OPTIMIZING MANAGEMENT OF SPINAL CORD COMPRESSION: INSIGHTS FROM MULTIDISCIPLINARY CLINIC OF THE TASHKENT MEDICAL ACADEMY - Shamsiyeva U. A.; Oltiboyev A. M. (Web of Journals Publishing, 2024)
This article provides insights into strategies for better managing spinal cord compression based on the experiences and practices observed at Clinic 2 of the Tashkent Medical Academy. In exploring clinical practices, diagnostic methodologies, treatment modalities, and rehabilitation approaches, the article is looking for contributions to improving patient care in complicated neurological conditions.
Keywords: Spinal Cord Compression, Clinical Assessment, Diagnostic Imaging, Surgical Intervention, Rehabilitation, Long-Term Management.